2021
DOI: 10.1177/0040517520982001
|View full text |Cite
|
Sign up to set email alerts
|

Structure–property relationship of melt spinning polypropylene fibers containing inorganic particulate CaCO3 fillers

Abstract: Spinning technology using melt extrusion and spin-draw processes transforms polymeric materials into highly oriented, crystallized polymeric fibers. Thermoplastic isotactic polypropylene compound with ground CaCO3 (GCC) and precipitate CaCO3 (PCC) with stearic acid surface coating treatment was used in this study. This product was developed in masterbatch form, which contained 70% GCC in resin and 50% PCC in resin. The resulting (masterbatch pellets) polymer can be spun into fibers through a single-screw extru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 18 publications
(40 reference statements)
0
6
0
Order By: Relevance
“…Wei et al's studies showed that the tensile strength of highly oriented polypropylene/multiwalled carbon nanotube (PP/MWCNT) composites prepared by die drawing was increased by 550%. [21] Die drawing can also reduce the material's density by forming voids. Rane et al [18] studied die drawn Talc-filled PP and die drawn unfilled PP with different drawing ratio.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wei et al's studies showed that the tensile strength of highly oriented polypropylene/multiwalled carbon nanotube (PP/MWCNT) composites prepared by die drawing was increased by 550%. [21] Die drawing can also reduce the material's density by forming voids. Rane et al [18] studied die drawn Talc-filled PP and die drawn unfilled PP with different drawing ratio.…”
Section: Introductionmentioning
confidence: 99%
“…Wei et al's studies showed that the tensile strength of highly oriented polypropylene/multi‐walled carbon nanotube (PP/MWCNT) composites prepared by die drawing was increased by 550%. [ 21 ]…”
Section: Introductionmentioning
confidence: 99%
“…When there are two phases, interstice around particles later bear high tension along fiber deformation would form as strength weak link along such as fibers in its stress–strain deformation. Furthermore, a two‐phase system in thermal calendar bonding inspect any cracks at weak interphase of filler‐polymer mixing phase 18 ; fiber strength depends on loading configuration in fibers 19 . Within the structure, particles may weaken fabric structure aspects as a form of the cavity, but the tenacity level will depend on structural factors.…”
Section: Resultsmentioning
confidence: 99%
“…The input parameters for single fibers tensile were recorded as the linear density of denier (gram/9000 m) in 1.5 denier to 10 denier. The previous articles have mainly documented the testing procedures 19 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation